Freud and Monotheism: Moses and the Violent Origins of Religion - Malabou, Catherine; Schwab, Gabriele; Sharviṭ, Gilʿad; Sharviṭ, Gilʿad; Whitebook, Joel; Assmann, Jan; Feldman, Karen S.; Bernstein, Richard; Hendel, Ronald S.; Goetschel, Willi; Segalovits, Yaʿel (Berkeley Forum in the Humanities, 2018)
Frontmatter -- Contents -- Introduction -- 1. “Why [the Jews] Have Attracted This Undying Hatred” -- 2. Geistigkeit: A Problematic Concept -- 3. Heine and Freud: Deferred Action and the Concept of History -- 4. Freud’s Moses: Murder, Exile, and the Question of Belonging -- 5. A Leap of Faith into Moses: Freud’s Invitation to Evenly Suspended Attention -- 6. Freud, Sellin, and the Murder of Moses -- 7. Creating the Jews: Mosaic Discourse in Freud and Hosea -- 8. Is Psychic Phylogenesis Only a Phantasy? New Biological Developments in Trauma Inheritance -- Contributors -- Index